4-3x=4(3-x)-3x

Simple and best practice solution for 4-3x=4(3-x)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-3x=4(3-x)-3x equation:


Simplifying
4 + -3x = 4(3 + -1x) + -3x
4 + -3x = (3 * 4 + -1x * 4) + -3x
4 + -3x = (12 + -4x) + -3x

Combine like terms: -4x + -3x = -7x
4 + -3x = 12 + -7x

Solving
4 + -3x = 12 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
4 + -3x + 7x = 12 + -7x + 7x

Combine like terms: -3x + 7x = 4x
4 + 4x = 12 + -7x + 7x

Combine like terms: -7x + 7x = 0
4 + 4x = 12 + 0
4 + 4x = 12

Add '-4' to each side of the equation.
4 + -4 + 4x = 12 + -4

Combine like terms: 4 + -4 = 0
0 + 4x = 12 + -4
4x = 12 + -4

Combine like terms: 12 + -4 = 8
4x = 8

Divide each side by '4'.
x = 2

Simplifying
x = 2

See similar equations:

| -0.1875*8=-1.5 | | (x^2+5x+5)-(5x^2-8x+7)= | | 8*t=-1.5 | | -4.45-2=-5.5s-4.2 | | -7k-5(-7k+7)=-3+4(7-8k) | | 6*t=-9 | | 6*(-9)=t | | -(h+7)=-8 | | 12-4n=-(n+1)-5 | | (12y+14)+(-2y-3)= | | x/3+18=44 | | 10+x+5x=7x+2 | | 2x+33-5x=3-7x+2 | | (9x-1)-(4x+3)= | | 31=7(-5n-7)-4(2-6n) | | 3x^2-6x-(2-k)=0 | | .03y+.09(50000-y)=2490 | | (2x+5)+(4x-11)= | | -6(1+2x)=90 | | 1b+4b=8b-b | | 3t^2+14t+4=0 | | 2y-(7-5y)-21=0 | | 4-M=6 | | 400+2+3=1050 | | -0.441+x/2.2=0.922 | | 35+d=17 | | 50.00+3.75b=800 | | 50.00+3.75b=400 | | -16=x+47 | | -3/7+2k=-86/21 | | 32+d=17 | | 50.00+3.75=400 |

Equations solver categories